Innate-like behavior of human invariant natural killer T cells during herpes simplex virus infection - Novakova, Lucie; Nevoralova, Zuzana; Novak, Jan (Cellular immunology, 2012)
Invariant natural killer T (iNKT) cells, CD1d restricted T cells, are involved in the immune responses against various infection agents. Here we describe their behavior during reactivation of human herpes simplex virus (HSV). iNKT cells exhibit only discrete changes, which however, reached statistically significant level due to the relatively large patient group. Higher percentage of iNKT cells express NKG2D. iNKT cells down-regulate NKG2A in a subset of patients. Finally, iNKT cells enhance their capacity to produce TNF-α. Our data suggests that iNKT cells are involved in the immune response against HSV and contribute mainly to its early, innate phase.
Keywords: Female; lidé středního věku; Tumor Necrosis Factor-alpha; Antigens, CD1d; Adolescent; Lymphocyte Activation; Herpes Simplex; mužské pohlaví; Simplexvirus; Immunity, Innate; exprese genu; Humans; dospělí; antigeny CD1d; lidé; aktivace viru; Middle Aged; Virus Activation; přirozená imunita; senioři; TNF-alfa; aktivace lymfocytů; Natural Killer T-Cells; herpes simplex; NK Cell Lectin-Like Receptor Subfamily K; ženské pohlaví; Gene Expression; Aged; NKT buňky; Adult; Male; mladiství; lektinové receptory NK-buněk - podrodina K